Electrophysiology and psychophysiology in psychiatry and psychopharmacology - Bob, Petr; Boutros, Nash N.; Kumari, Veena (Current Topics in Behavioral Neurosciences, 2014)
Psychophysiology is an ever expanding field. The application of psychophysiological investigations to psychiatric disorders is likewise expanding and has in fact shed much light on some of the neural processes contributing to the development of psychiatric symptoms and/or their amelioration following treatment. The first part of this volume deals with a number of conditions where psychophysiological investigations have recently provided some insight into the pathophysiology of a particular manifestation (e.g., dissociation) or a disorder. Although this volume has a main focus on electrophysiological investigative modalities where neuroimaging was complimentary this added insight was included. The second part of the volume focuses on novel uses of psychophysiological measures, combining it with neuropsychology and imaging where possible, in the context of neuropsychiatric research and describes advanced analytical tools.  Both basic and clinical investigators in this field should find the reviews and interpretations provided clear and informative. Clinicians will find this volume easy to assimilate. While direct clinical applications may be down the road, the insights provided should help the practicing clinicians to have firmer understanding of the complexity of the disorder they manage in everyday practice.